STUDI SURFACE COATING DAN KARAKTER FISIS LAPIS TIPIS NANO PARTIKEL TiO2 PADA KULIT FINISH - Prasetyo Hermawan; Swatika Juhana (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
Influence of variation; type of film material, number of film layers and concentration of TiO2. The purpose of this research was to study of variations; type of film materials, number of film layers and concentration of TiO2 on goat skin finish. The variation in the number of layers are; 0, 1, 2 and 3 layers, while variations in the concentration of TiO2 are; 0%, 0.5%, 1%, 1.5% and 2%. Films are made using polymers from water soluble nitrocellulose (NC-W), water soluble polyurethane (PU-W) and thinner soluble polyurethane (PU-T). Furthermore, testing of the physical characteristics of the skin includes; weight, thickness, softness, hardness and contact angle. In the variation of the number of film layers from zero to three layers, the largest increase in skin weight occurred in the use of PU-T, namely 0.47 gr and the smallest in NC-W of 0.28 gr. The increase in thickness also occurred at P-UT, which was 43.60 µm and the lowest at PU-W was 15.66 µm. The largest decrease in skin softness occurred in PU-T from 1.88mm to 1.40 mm (down 0.48 mm) and the smallest in PU-W, which was down by 0.06mm. The hardness of the skin layer using PU-T increased from 88.66HA to 95.50HA (up 6.84 HA) and the lowest in PU-W increased by 5.5HA. The change in the contact angle of the leather surface for PU-T decrease from 770 to 490 (down 280) and the lowest for PU-W from 800 to 630 (down 170). In the variation of TiO2 concentration from 0% to 2%, the largest increase in skin weight occurred in PU-T, namely 0.13 gr and the smallest in PU-W of 0.07 gr. The change in contact angle at the variation of TiO2 concentration was not significant, the mean value of the contact angle for; NC-W, PU-W and PU-T are; 61.00, 62.20 and 58.40.